Benzylene-linked [PNP] scaffolds and their cyclometalated zirconium and hafnium complexes - Sietzen, Malte; Batke, Sonja; Antoni, Patrick W.; Wadepohl, Hubert; Ballmann, Joachim (Dalton transactions, 2017)
The benzylene-linked [PNP] scaffolds HN(CH2-o-C6H4PPh2)2 ([A]H) and HN(C6H4-o-CH2PPh2)2 ([B]H) have been used for the synthesis of zirconium and hafnium complexes. For both ligands, the dimethylamides [A]M(NMe2)3 ([A]1-M) and [B]M(NMe2)3 ([B]1-M) were prepared and converted to the iodides [A]MI3 ([A]2-M) and [B]MI3 ([B]2-M) (M = Zr, Hf). Starting from these iodides, the corresponding benzyl derivatives [A]MBn3 ([A]3-M) and [B]MBn3 ([B]3-M) (M = Zr, Hf) were obtained via reaction with Bn2Mg(OEt2)2. For zirconium, the benzylic ligand positions in [A]3-Zr and [B]3-Zr were found to cyclometalate readily, which led to the corresponding κ4-[PCNP]ZrBn2 complexes [A]4-Zr and [B]4-Zr. As these complexes failed to hydrogenate cleanly, cyclometalated derivatives with only one alkyl substituent were targeted and the mixed benzyl chlorides κ4-[PCNP]MBnCl ([B]5-M, M = Zr, Hf) were obtained in the case of ligand [B]. Upon hydrogenation of [B]5-Zr, the η6-tolyl complex [B]Zr(η6-C7H8)Cl ([B]6-Zr) was generated cleanly, but the corresponding hafnium complex [B]5-Hf was found to decompose unselectively in the presence of H2. Using a closely related carbazole-based [PNP] ligand, Gade and co-workers have shown recently that zirconium η6-arene complexes similar to [B]6-Zr may serve as zirconium(II) synthons, namely when reacted with 2,6-Dipp-NC (L) or pyridine (py). Both these substrates were shown to react cleanly with [B]6-Zr, which led to the formation of the bis-isocyanide complex [B]ZrCl(L)2 ([B]7-Zr) and the 2,2′-bipyridine derivative [B]ZrCl(bipy) ([B]8-Zr), respectively. Upon reaction of [B]Zr(η6-C7H8)Cl ([B]6-Zr) with NaBEt3H, the cyclometalated derivative κ4-[PCNP]Zr(η6-C7H8) ([B]9-Zr) was isolated. In an attempt to synthesise terminal hydrides, complexes [A]MI3 ([A]2-M) were treated with KBEt3H, which led to the isolation of the cyclometalated hydrido complexes κ4-[PCNP]M(H)(κ3-Et3BH) ([A]10-M; M = Zr, Hf) featuring a κ3-bound triethyl borohydride moiety.